DISCOLOURATION OF COATED MODIFIED OAK WOOD DURING SIMULATED INDOOR SUNLIGHT EXPOSURE - Mikleĉić, Josip; Jirouš-Rajković, Vlatka; ĐurĊevac, Haas (Innovation in Woodworking Industry and Engineering design, 2012)
The aim of this work was to establish a degree to which UV irradiation causes discolouration of heat-treated and ammonium-treated wood. Discolouration of uncoated samples and of those treated with commercial transparent coatings (oil, UV varnish, water-based and polyurethane varnish) was measured. The most significant colour changes (ΔE*) was recorded be-tween uncoated samples and those coated with water-based varnish, whereas other coatings, most of all two-component polyurethane varnish, had helped reduction of discolouration. The ammonium-treated oak wood showed superior stability to discolouration.